The occurrence of oral-mucosal lesions among employees of a steelmill--a preliminary study - Zain, R.B.; Koh, L.S. (1988)
A study has been conducted on 198 employees of a steel-mill industry. These participants were examined for mucosal lesions in the oral cavity and including the commissures and vermillion borders of the lips. The prevalences of 16 types of lesions are reported.